Legal Implications of FATCA in Indonesia: An Analysis of the Viability of the IGA Model 1C Approach - Anggia, Putri; Riyanto, Aisyah Ajeng Putri; Yunita, Ani; Astuti, Wuku (Jambura Law Review, 2026)
This article critically examines the implementation of FATCA in Indonesia and its implications for national legal sovereignty, the principle of bank secrecy, and personal data protection. Although FATCA operates as a unilateral U.S. regime with extraterritorial effects, its enforcement through IGAs has pressured states to reconcile global tax transparency obligations with domestic legal frameworks. Using normative legal research, this study analyzes statutory instruments, international agreements, and institutional practices to evaluate the viability of IGA Model 1C within the Indonesian legal framework. The study finds that Indonesia has not merely complied with FATCA but has adopted a mediated approach through the IGA Model 1C framework, conceptualized as the Hybrid Sovereignty Compliance Model. The findings demonstrate that the IGA Model 1C approach constitutes a legally and institutionally viable mechanism. It enables compliance with FATCA while preserving regulatory control through domestic legal authority and institutional coordination. Sovereignty is maintained through three key indicators: the use of domestic legal authority as the basis for data disclosure, the presence of institutional gatekeeping mechanisms, and the alignment of FATCA obligations with multilateral frameworks, particularly the OECD-led AEOI mechanism, which is operationalized through the CRS. This study contributes to the literature by offering a doctrinal and policy-oriented framework for understanding how developing states can strategically navigate asymmetrical global tax regimes while maintaining constitutional and regulatory integrity.